2022
DOI: 10.1007/s00268-022-06549-2
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in Surgical Care in Low‐ and Middle‐Income Countries: A Scoping Review

Abstract: Background Access to timely and quality surgical care is limited in low- and middle-income countries (LMICs). Telemedicine, defined as the remote provision of health care using information, communication and telecommunication platforms have the potential to address some of the barriers to surgical care. However, synthesis of evidence on telemedicine use in surgical care in LMICs is lacking. Aim To describe the current state of evidence on the use and distribution of tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 247 publications
0
10
0
Order By: Relevance
“…Adherence to close follow-up of BMS patients is important but challenging beyond 2 years, where the rate is reported to be 40–62% [ 31 33 ]. We observed in the current study, as in most other BMS studies, that the rate of postoperative patient-reported dietitian interaction and routine blood testing was quite low.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to close follow-up of BMS patients is important but challenging beyond 2 years, where the rate is reported to be 40–62% [ 31 33 ]. We observed in the current study, as in most other BMS studies, that the rate of postoperative patient-reported dietitian interaction and routine blood testing was quite low.…”
Section: Discussionmentioning
confidence: 99%
“…This possible explanation is supported by the World Bank report, “The Health Workforce in Ethiopia”, which shows Ethiopia is one of the countries with a very low health workforce, five times below the minimum threshold of 4.45 per 1000 population set by the World Health Organization to achieve the SDG Health. 37 …”
Section: Discussionmentioning
confidence: 99%
“…While the use of telemedicine for surgical care has been emerging in LMICs and has been shown to streamline the follow-up care of CHD patients, this data is not captured withing the IQIC database. 20 21 Another limitation was the small sample size for quantitative analysis and that there was variation in the timing of the impact of the pandemic on various programmes, which only compared data between March and November in 2019 vs 2020. Further studies should be conducted regarding the effects of COVID-19 on paediatric cardiac critical access centres at later time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the role of telemedicine was not adequately explored among the participating sites. While the use of telemedicine for surgical care has been emerging in LMICs and has been shown to streamline the follow-up care of CHD patients, this data is not captured withing the IQIC database 20 21. Another limitation was the small sample size for quantitative analysis and that there was variation in the timing of the impact of the pandemic on various programmes, which only compared data between March and November in 2019 vs 2020.…”
Section: Discussionmentioning
confidence: 99%